Body image perception in athletes versus non-athletes - Rodgers, Emily; Blum, Megan; Johnson, Beth (My University, 2010)
The purpose of this study was to find if there was a relationship when measuring body image perception between athletes and non-athletes.
10 p. Includes bibliographical references (p. 10)
Keywords: BMI; Non-athletes; University of Wisconsin-River Falls--Athletics; College students--Health and hygiene; University of Wisconsin-River Falls--Students; Body mass index; College students; Body image; Self-perception; Athletes